Menuntut Ilmu sebagai Penghapus Dosa-dosa Masa Lalu: Studi Hadis - Neni Suryani; Ilim Abdul Halim; Dadang Darmawan (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the hadith about studying. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about seeking knowledge in the hadith narrated by al-Tirmidhi No. 2572. The results and discussion of this study indicate that the status of hadith has the quality of hasan li ghairihi with the qualifications of maqbul ma'mul bih for the practice of Islam. This study concludes that the hadith riwatat al-Tirmidhi No. 2572 is relevant to be used as a holistic development of knowledge covering the goals of the world and the hereafter.